Perlindungan Data Peserta BPJS Kesehatan Sebagai Hak Asasi: Tinjauan Hukum Dan Tanggung Jawab Negara - Jaya, Beni Parawira Candra; Tisnanta, HS; Putri S, Ria Wierma (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2025)
In the digital age, the management of BPJS Kesehatan participants' personal data faces serious security challenges, including the risk of data leaks that could damage public trust and have widespread socio-economic impacts. This study discusses the strategic steps that BPJS Kesehatan and the government must take to improve the security of participant data. Key efforts include strengthening information technology infrastructure with layered security systems, integrating data with relevant agencies using biometric technology, and increasing awareness and training on data protection for all parties involved. Additionally, the importance of adaptive regulations, strict enforcement of laws, rapid response mechanisms for incidents, and routine security audits are also key focuses. Investment in advanced technologies such as artificial intelligence and machine learning is essential to anticipate increasingly complex cyber threats. A holistic approach involving national and international collaboration and the development of an inclusive digital ecosystem is expected to maintain the integrity of participant data and improve the quality of national health services. Thus, the National Health Insurance program can continue to be trusted by the public in facing the dynamics of healthcare service digitalization.